Marvel and Artefact : The 'Wonders of the East' in Its Manuscript Contexts - Ford, A. J. (Library of the Written Word - the Manuscript World Ser, 2015)
Marvel and Artefact: The 'Wonders of the East' in Its Manuscript Contexts -- Copyright -- Dedication -- Contents -- Acknowledgements -- List of Figures and Tables -- List of Abbreviations -- 1: 'The Manifold Uses of Things': The Early Medieval Book as Artefact -- 2: The Wonders of the East and the Learned Tradition of Marvels -- Introduction -- A Brief Overview of the Learned Tradition -- The 'Wonders of the East' and the 'Letter of Pharasmenes to Hadrian' -- 3: The Wonders in a Manuscript of Unknown Origin: London, British Library, Cotton Vitellius A. xv -- Introduction -- Illustration -- Homodubii -- Cynocephali and Donestre -- Other Similarities -- Conclusion -- Palaeography -- Anglo-Saxon Square Minuscule: Scribe 2 -- Style-I English Vernacular Minuscule: Scribe 1 -- The Significance of Distinct Scripts in Vitellius A. xv -- Codicology -- The Consensus Quires -- The Contested Quires -- The 'Wonders' in Vitellius A. xv: 'Speaking Beyond the Light' -- 4: The Wonders and the Computus Manuscript: London, British Library, Cotton Tiberius B. v -- Introduction -- The Origin and Audience of Tiberius B. v -- Reading Books and the Monastic Library -- The Materiality of Tiberius B. v -- Page Design in Tiberius B. v -- The 'Wonders of the East' -- The Calendar -- Tiberius B. v: The Semiotics of the 'Computus' Manuscript -- The 'Wonders of the East' as Semiotic -- The Land of Vineyards and the Ivory Couch -- The Mountain of Adamant and the Griffin -- The Phoenix and Its Nest of Cinnamon -- The Unnamed Fiery Mountain and Its Black Inhabitants -- Jamnes and Mambres -- Conclusion -- 5: The Wonders and the Schools: Oxford, Bodleian Library, Bodley 614 -- Introduction -- The Problem of Dating Bodley 614 -- Codicological Considerations -- Art-Historical Considerations -- Palaeographical Considerations -- Textual Considerations -- Summary.